Respuesta :

Input 7 for every x so
f(7) = -2 (7)^2 +4
f(7) = -2(49) +4
f(7) = -98 +4
f(7) = -94

Answer:

x= 1.3

Step-by-step explanation:

You have to plug in 7 so it will look like:

f(x) = -2x² + 4

7(x) = -2x² +4

now what you have to do is multiply 7 by x which will get you

7x = -2x² + 4

now because you have that you want to multiply -2 twice because you have that ²

7x = 4x +4

now you want to move the 4x and you can do that by doing the inverse operation and in this case since its a positive 4 you may want to subtract 4x from 4x and 7x

3x=4

now you want to divide 4 from 3  and you get 1.333333333333333

hope this helps